Publish and be damned: how to be an underground institutional publisher - Bodman, Sarah (PORTO ARTE: Revista de Artes Visuais, 2013)
The Centre for Fine Print Research (CFPR) at the University of the West of England, Bristol UK publishes reference materials on contemporary printmaking and related areas for an international audience. Three of its established publications focus on artists’ books: the biennial “Artist’s Book Yearbook”, “The Blue Notebook” journal for artists’ books, and the free download “Book Arts Newsletter”. In this article, the editor of these three publications reflects upon how they were established, and some of the successes, trials and tribulations of publishing under an institutional imprint. From conception, content and design, to funding, print and distribution of hard copy and digital download, to their international base of readers.